2006
DOI: 10.3162/036298006x201797
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Party and Ideology on Roll‐Call Voting in State Legislatures

Abstract: To assess the relative impact of party and ideology on legislative behavior, I utilize survey-based measures of legislator ideology to examine voting in five state legislatures. The results suggest that, although party and ideology both influence voting, the impact of party is greater. The magnitude of this impact varies, however, from chamber to chamber. The activity of parties in the electoral arena explains part of this variance, with more active parties having more influence. Thus, research on legislative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 23 publications
(16 reference statements)
1
33
0
Order By: Relevance
“…This is not the case at the state level where there are variations among both majority party status and leadership power, which allow for an examination of the relative impact of both variables. A few recent studies have examined party influence in state legislatures (Jenkins 2006;Wright and Shaffner 2002), but while they establish that parties influence legislative behavior in the states and that this influence varies from state to state, they are limited because they do not examine how parties influence voting or why this influence varies from state to state. Thus, there is a need to test these theories at the state level to determine their general applicability in settings other than Congress and to understand how it is that parties influence voting in the U.S. states.…”
Section: Other Considerationsmentioning
confidence: 99%
“…This is not the case at the state level where there are variations among both majority party status and leadership power, which allow for an examination of the relative impact of both variables. A few recent studies have examined party influence in state legislatures (Jenkins 2006;Wright and Shaffner 2002), but while they establish that parties influence legislative behavior in the states and that this influence varies from state to state, they are limited because they do not examine how parties influence voting or why this influence varies from state to state. Thus, there is a need to test these theories at the state level to determine their general applicability in settings other than Congress and to understand how it is that parties influence voting in the U.S. states.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Clucas (2009) found that perceived power was significantly associated with measures of polarization in the electorate, but not with professionalization. Shannon Jenkins (2006) found evidence from three election cycles in five states that party exerted a stronger influence on roll-call voting where the party was more electorally active. Martorano (2004) examined a sample of 23 chambers from 1955 to 1995 and found that larger majorities are associated with fewer minority rights, and that party strength responded to the use of joint rules but not to professionalism.…”
Section: Why Are Some Parties Stronger Than Others?mentioning
confidence: 99%
“…Studies in this vein typically ask to what extent some observed characteristic, usually derived from roll calls, is consistent with party power. Analyses designed to answer Krehbiel's challenge have not been extended to the state legislatures until recently (Shannon Jenkins 2006, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kousser, lewis, and Masket (2007) estimated NoMiNate scores for California assembly members, to investigate whether legislators changed their voting behavior after the 2002 gubernatorial recall election. Jenkins (2006) estimated NoMiNate scores for 5 state legislatures and used an external survey to measure the effect of parties on voting. to examine the effects of single-member versus multimember districts on legislator extremism, Bertelli and richardson (2008) created NoMiNate scores for the arizona legislature.…”
mentioning
confidence: 99%